Funciones desempeñadas como asistente de tesorería, asistente contable y analista contable en Inversiones Inmobiliarias Mar S.A.C. – Hotel El Gran Marqués - Lázaro Calua, Hector Alonso (2020)
The following report explains the functions performed as an Accounting Assistant and as Accounting Analyst during the period of September 2014 to date, in Inversiones Inmobiliarias Mar S.A.C. company - Hotel El Gran Marqués., For more than four years, professional performance has been shown performing different functions in the different positions of the accounting and HR area, demonstrating everything learned during the student stage at the School of Accounting and Finance. This report begins the historical review of the company, the corporate values that are to be implemented in each worker, the structure of the company and the area where it performs the functions of Accounting Assistant and Accounting Analyst, the problem of each area and proposed some solutions in accordance with the theoretical framework and what has been learned as a student in the courses: Accounting Doctrines, Accounting I, II and III, Tax Accounting, Higher Accounting I, II, Internal Audit, Tax Audit and Financial Analysis and Research I, II, the critical evaluation is also made to the professional training due to the curriculum and proposals are presented to improve the curricular mesh of our school of accounting and as a final part the conclusions and recommendations of the present work, as well as the bibliographic references and annexes which contain images of some functions that were performed during this period of my work experience.